NUMERICAL SOLUTION OF GLIOMA GROWTH MODELS USING TWO-STAGE SUCCESSIVE OVER-RELAXATION METHOD - HUSSAIN, ABIDA (2019)
Glioma, emerges from the glial cells, is the most invasive primary brain cancer. Several mathematical models have been developed to describe the proliferation and diffusion properties of glioma growth. Among the existing models, reaction-diffusion models are the most reliable.